Analisis Penerapan Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil, dan Menengah (SAK-EMKM) Pada Usaha Kecil Namira Bakery di Kabupaten Enrekang - Nur Fadillah; Sahade; Samsinar (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of financial reporting at the small business Namira Bakery in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities. The research method used is descriptive qualitative, employing an analytical approach to data collected in both written and oral forms. The focus of the study is to assess the extent to which Namira Bakery’s financial reports comply with the requirements of SAK EMKM. Data collection techniques include interviews, documentation, and observations related to the financial records of Namira Bakery. The research results indicate that the financial statements of the small enterprise Namira Bakery do not yet fully comply with the provisions of SAK EMKM. The business still uses a simple bookkeeping system that only documents cash inflows and outflows, without generating any formal financial statements. Namira Bakery has not prepared the three main financial reports required by SAK EMKM, namely the income statement, the statement of financial position (balance sheet), and the notes to the financial statements.